Musae Radix Sebagai Inovasi Pemberdayaan Ekonomi: Studi: Mualaf di Desa Bulu Lor Kecamatan Jambon Kabupaten Ponorogo - Fitriani, Hanik; Kususiyanah, Anjar (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
Bulu Lor Village is one of the villages in Jambon Sub-District, in this village there are recent converts of Buddhism to Islam. The proliferation of Buddhism in this region because of its neat preaching management and supported by sufficient funding, and caused by economic and religious understanding weakness of Muslims in that area. There are 510 of 4000 farmers or farm laborers in Bulu Lor Village who rely on their economy from harvest. There are 25 converts to Islam in Bulu Lor Village, Jambon Subdistrict, Ponorogo Regency and included as marginal or disadvantaged groups in terms of economic welfare. This type of research was Participatory Action Research conducted by providing assistance in the form of training in processing banana humps to become high-value economic products as an alternative effort to increase household income, hopefully pre-prosperous converts become prosperous and faithful to Islam.